Moral economy: What’s in a name - Carrier, James G (Anthropological theory, 2018)
The idea of moral economy has been increasingly popular in the social sciences over the past decade, given a confusing variety of meanings and sometimes invoked as an empty symbol. This paper begins by describing this state of affairs and some of its undesirable corollaries, which include unthinking invocations of the moral and simplistic views of some sorts of economic activity. Then, referring especially to the work of EP Thompson and James C Scott, this paper proposes a more precise definition of moral economy that roots moral economic activity in the mutual obligations that arise when people transact with each other over the course of time. It thus distinguishes between the moral values that are the context of economic activity and those that arise from the activity itself. The solution that the paper proposes to the confused state of ‘moral economy’ can, therefore, be seen as terminological, as the sub-title suggests, but it is intended to have the substantive benefits of a better approach to economic activity and circulation and a more explicit and thoughtful attention to moral value.